OF EFFECT OF SOME SOIL TILLAGE SYSTEMS ON TILLAGE APPEARANCE AND SOME TECHNICAL INDICATORS MACHINARY UNITS - & Saadoon, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The experiment was conducted on a farm of the College of Agriculture - University of Baghdad for the year 2015 in silt-clay loam soil in order to evaluate the effect of tillage equipment on tillage appearance and some the technical indicators. The tractor" ITM– 285"with tillage systems implements tow factors included, three primary tillage implements included: Moldboard plow, Chisel plow and sweep plow and three pulverization implement included :disc harrow, spring spike tooth harrow and rotary harrow studying the effect of these factors on: Number of clods > 10cm , number of clods < 5cm, disturbed soil volume ,and total porosity in this reseach . Treatment were Laid out using split –plot with randomized complete block design in three replicates. The results showed that sweep plow  superior in obtained less number of clods > 10cm/m2 which was 12.7 clod/m2, less number of clods > 5cm/ m2 which was 21.28 clod/m2  and  highest soil porosity which was 57.11% compared with chisel plow and moldboard plow , chisel plow showed the superior in getting higher disturbed soil volume which was 663.3m3/ hr compared with other plows. Rotary harrow obtained less number of clods > 5cm/m2 which was 25.06 clod / m2, less soil porosity which was 54.78% compared with disc harrow and spring spike tooth harrow. Spring Spike tooth Harrow obtained highest disturbed soil volume which was 1021.4 m3/ hr. The interference between sweep plow with rotary harrow got less number of clods > 5cm/m2 which was 16.83 clod/m2, mean while chisel plow with spring spike tooth harrow got highest disturbed soil volume which was1027.8 m3/ hr, while sweep plow with spring spike tooth harrow was superior to obtain highest soil porosity which was 58.67 %.